Biological effects of L-carnitine on ovine oocyte maturation and embryo development: Oocyte maturation and embryo culture - Darzi nia, Abbase; Zandi, Mohammad; Ghaedrahmati, Annahita (Cellular and Molecular Biology, 2025)
This study was conducted to determine the effects of L-carnitine on in vitro ovine maturation and early embryo development. In the first experiment, oocytes were matured in TCM-199 medium with different concentrations of L-carnitine (0, 0.125, 0.25, 0.5, 1, 2, and 4 mM) and after fertilization, presumptive zygotes were cultured for 9 days on mCR2aa medium. In the second experiment, oocytes were matured in a maturation medium with various concentrations of L-carnitine (0, 0.125, 0.25, 0.5, 1, 2, and 4 mM). After fertilization, presumptive zygotes were cultured in a culture medium containing various L-carnitine concentrations (0, 0.125, 0.25, 0.5, 1, 2, and 4 mM). In vitro maturation (IVM) was carried out in a humid atmosphere of 5% CO2, 5% O2, and 90% N2 at 38.5 °C, and for in vitro culture (IVC), the concentration of O2 decreased to 5%. Morula and blastocyst development was evaluated on days 5 and 9, respectively. The results of the first experiment showed that the concentrations of 0.125, and 0.25 mM L-carnitine numerically led to an increase in the percentage of morula, blastocyst, and hatched blastocyst compared with control. The percentage of blastocyst formation increased at concentrations of 0.125 mM and 0.25 mM (31.97 ± 0.74 and 31.60 ± 1.39, respectively) compared with the control treatment (29.44 ± 2.42) (p>0.05). The results of the second experiment showed that the different concentrations of L-carnitine, simultaneously in the maturation and culture media of ovine embryos, similar results were observed when it was used only in the maturation medium, and the percentage of blastocyst formation increased at concentrations of 0.125 mM and 0.25 mM (35.62 ± 0.45 and 35.04 ± 1.70, respectively) compared to the control treatment (31.56 ± 3.39) (p>0.05). In conclusion, the use of L-carnitine in the media for oocyte maturation and embryo culture is recommended.